Analisis Perbandingan Kinerja Keuangan Sebelum dan Sesudah Adopsi Tata Kelola Teknologi Informasi (Pada Perusahaan Manufaktur dan Pertambangan yang Terdaftar di BEI) - Aninda Puji Adila; Raudhatul Hidayah (Syntax Literate, 2023)
The objective of this study is to test and to prove whether companies that have adopted information technology (IT) governance mechanisms have improved their financial performance, by measuring profitability, productivity and market value pre and post adoption. Manufacturing and mining companies listed on the Indonesia Stock Exchange are the population of the research by using event study methodology. Researcher employs secondary data in the form of corporate annual reports that gotten by firm's official website. The SPSS 26 application used to process the data by testing hypotheses through descriptive statistics, normality tests and paired sample t-test. According to the study's findings, there were no appreciable changes between the financial performance of mining and manufacturing companies before and after adopting IT governance. Two of the eight indicators—asset turnover and share repurchase—have a considerable divergence from one another.